Memetakan Efikasi Diri Akademik Mahasiswa Gen Z: Kajian Komparatif berdasarkan Gender dan Status Pekerjaan - Andriani, Iin; Khumaidatul Umaroh, Siti; Yeremia Alexander Govicar, Dengah (Faculty of Ushuluddin and Humanities, 2025)
This consider points to analyze contrasts in scholastic self-efficacy among Era Z understudies based on sex and work status. Self-efficacy, an individual's conviction in their capacity to oversee activities to realize particular objectives, is impacted by different components, counting encounter and social environment. This think about included 205 understudies in East Kalimantan, measured utilizing the Indonesian form of The Scholastic Self-Efficacy Scale (TASES). Information were analyzed utilizing an free t-test. The comes about appeared no noteworthy contrast in scholastic self-efficacy between male and female understudies. In any case, working understudies shown higher scholastic self-efficacy compared to non-working understudies. These discoveries highlight the part of work involvement in improving down to earth abilities and self-confidence among understudies, as well as the require for comprehensive scholastic bolster for Era Z.